2021
DOI: 10.3389/fpubh.2021.710633
|View full text |Cite
|
Sign up to set email alerts
|

Can Sound Health Insurance Increase the Internal Circulation in the Economy of China?

Abstract: In 2020, President Xi Jinping put forward a constructing cycle that has been given priority in this study. This particular cycle, when considered within the inner loop and outer loop, promotes the guiding ideology of the new development pattern of the binary economy that exists in recent times. Therefore, to gauge the extent of the promotion of domestic production and consumption, from the perspectives of medical expenses, this study refers to the bootstrap rolling window causality method, which considers the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…This channel of interaction is significant as it highlights the potential role of labor insurance in mitigating the adverse effects of air pollution on worker productivity. Furthermore, other research has indicated that investing in insurance necessities can have a cumulative effect on promoting economic growth [16].…”
Section: Introductionmentioning
confidence: 99%
“…This channel of interaction is significant as it highlights the potential role of labor insurance in mitigating the adverse effects of air pollution on worker productivity. Furthermore, other research has indicated that investing in insurance necessities can have a cumulative effect on promoting economic growth [16].…”
Section: Introductionmentioning
confidence: 99%